Pengaruh Financial Literacy, Financial Attitude Dan Pendapatan Terhadap Perilaku Pengelolaan Keuangan Pada UMKM Fashion Di Kota Malang - Nurul Khoirini; Ronny Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2021)
Abstract The purpose of this study was to partially between the influence of financial literacy, financial attitude and income towards financial management behavior on MSME fashion actors in city Malang. The population used in this study is MSME fashion practitioners in city Malang, totaling 5000 business actors while The sampling technique uses purposive sampling method with predetermined criteria of 50 business actors, with the sampling technique by distributing questionnaires. This type of research is explanatory research using a quantitative approach. Data analysis using multiple linear regression, test instruments, classic assumption tests, partial tests (t test) and hypothesis testing using the SPSS program. The results showed financial literacy (X1) and income (X3) influences financial management behavior (Y), while financial attitude (X2) does not affect financial management behavior (Y). Keyword: Financial Litercy, Financial Attitude, Income, Financial Management Behavior